Chosen aspects of threatened moss species occurrence in urban areas - a case study of Katowice - Fojcik, Barbara; Stebel, Adam (Biodiversity: Research and Conservation, 2006)
Fifty eight moss species were noted in the area of Katowice, which have been listed as threatened locally or threatened in the country. Almost 80% of these are rare species, which occur in up to 5 localities within the area discussed. They are scattered all over the town. However, their density distinctly increases in forest areas (up to 5 species per 1 km2). Their habitat preferences, synanthropization degree, as well as dynamic tendencies, are analysed in the paper presented. An interesting group of species consists of those recorded xclusively in anthropogenic habitats - especially those occurring on a concrete, rock-like substrate or on epigeic initial habitats. Very characteristic is the distribution of Weissia controversa - it grows only in abandoned, barren places around a zinc and lead smelting works, where the substrate pH ranges from 7 to 8. It should be noted that 3 localities of Discelium nudum were recorded - a moss which not so long ago ceased to be considered as extinct in Poland.